INDUSTRIAL PERSPECTIVES OF LACTIC ACID BACTERIA FOR BIOPRESERVATION AND FOOD SAFETY - A. Akbar; I. Ali; A. K. Anal (Journal of Animal and Plant Sciences, 2016)
Consumers are becoming more attentive towards the ingredients and preservation methods used for food preservation and pathogens control. The rapid globalization and use of chemical preservatives have changed the behaviors of foodborne pathogens. One of the most emerging problems is resistance to antibacterial compounds. Innovative and alternative approaches are getting appraisal to combat with the common and resistant foodborne pathogens in order to get maximum food safety in environment friendly manners. Amongst different alternative methods, one more interesting and widely acceptable method is the use of living probiotic bacteria or its acceptable metabolites for food biopreservation. The biopreservation phenomenon is the use of beneficial microbes and their products for food safety. Lactic acid bacteria have a potential to be used for food preservation due to their probiotic capabilities. They have been successfully used for the production and safety of foods including; meat, milk and vegetables. Lactic acid bacteria are amongst the beneficial microbes, which can also enhance the food taste and aroma,other than food safety against unwanted bacteria. The objective of this review is to cover and summarize the use of lactic acid bacteria for food safety and biopreservation.
Keywords: Food safety. Bio-control. Protective culture. Antimicrobials. Biopreservatives. Foodborne pathogens